2021
DOI: 10.1016/j.sjbs.2021.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the therapeutic potential of Hibiscus rosa sinensis synthesized cobalt oxide (Co3O4-NPs) and magnesium oxide nanoparticles (MgO-NPs)

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…The probability analysis of C. pipiens larval mortality using the nanoparticles was illustrated in Figure 6 b [ 34 ]. These results are consistent with Kainat et al (2021) [ 35 ], who reported that Co 3 O 4 nanoparticles have larvicidal potential for Aedes aegypti with 67.2 ± 1.7% mortality at 400 ppm compared with MgO NPs of 49.2 ± 8.1% mortality at the same concentration. The impact of cobalt oxide nanoparticles on the treated larvae is a shape-dependent activity.…”
Section: Resultssupporting
confidence: 92%
“…The probability analysis of C. pipiens larval mortality using the nanoparticles was illustrated in Figure 6 b [ 34 ]. These results are consistent with Kainat et al (2021) [ 35 ], who reported that Co 3 O 4 nanoparticles have larvicidal potential for Aedes aegypti with 67.2 ± 1.7% mortality at 400 ppm compared with MgO NPs of 49.2 ± 8.1% mortality at the same concentration. The impact of cobalt oxide nanoparticles on the treated larvae is a shape-dependent activity.…”
Section: Resultssupporting
confidence: 92%
“…The same phenomenon was observed in the case of both the uncalcined and leaf extract; the only difference is the slight shift in the location of the peaks. This again confirms that the extract has played a great role to prevent the overgrowth of Co 3 O 4 NPs during the synthesis process [ 33 – 35 ]. It is possible to elucidate the formation of Co 3 O 4 NPs with many surface hydroxyl function groups.…”
Section: Resultssupporting
confidence: 58%
“…While, the prominent levels of absorption peak located at around 2911 cm −1 reveal the presence of C-H stretching vibrations of an aromatic aldehyde. The peak observed around 2322 cm −1 represents the amide (C ≡ N) functional groups [ 33 ]. The medium absorption peak observed at 1638 cm −1 corresponds to C = O peak, which indicates the ketone functional group and also the ammine functional group.…”
Section: Resultsmentioning
confidence: 99%
“…(3) MgO NPs are formed following the calcination of magnesium tannic acid complexes at a high temperature of 400 • C. It is widely accepted that plants synthesise MgO NPs through these mechanisms. Biosynthesis of MgO NPs by the reaction of 3 g magnesium sulphate and 50 mL Hibiscus rosa-sinensis leaf extract was introduced by Khan and co-workers [85]. Moreover, Abdallah et al [87] investigated the antibacterial properties of NPs and the synthesis of MgO nanoflowers using rosemary extract without the intervention of chemical catalysts.…”
Section: Bio-templates-mediated Synthesis Strategies 21 Plant Extractsmentioning
confidence: 99%